"I'm Being a Man Here": Urban Boys' Performances of Masculinity and Engagement With Science During a Science Museum Visit. Issue 3 (2nd July 2016) - Archer, Louise; Dawson, Emily; Seakins, Amy; DeWitt, Jennifer; Godec, Spela; Whitby, Christopher
Abstract : The importance of increasing and widening participation in post-compulsory science and informal science learning (ISL) spaces is widely recognized—particularly for working-class and minority ethnic communities. While there is a growing understanding of the intersection of femininity with class, ethnicity, and science learning across formal and informal settings, there has been little work on how masculinity may shape urban boys' science (non)participation and (dis)engagement. This article analyzes performances of masculinity enacted by 36 urban, working-class boys (from diverse ethnic backgrounds) during school science museum visits, exploring how these performances relate to science identity and engagement. We identify three main performances of masculinity enacted during the visits ("laddishness, " "muscular intellect, " and "translocational masculinity"), and trace the implications of each for boys' science engagement. We consider the power implications of these performances, notably the extent to which hegemonic masculinity is normalized within the science museum space, the ways in which this normalization is co-constitutive of the boys' performances of masculinity, and the implications of the boys' performances of masculinity for other students (notably girls and less dominant boys). The article concludes with implications for research, policy, and practice regarding how to promote equitable participation and science learning within ISL.